Karamzin Returns to France - Sara Dickinson (Вивліоѳика, 2025)
Review of: Nikolai Karamzin, Lettres d’un voyageur russe. Introduction, translation, notes and commentary by Rodolphe Baudin. Paris, Institut d’Études Slaves, 2022